Analysis of Brain Nuclei Accessible to Ghrelin Present in the Cerebrospinal Fluid - Cabral, Agustina Soledad (2013)
Ghrelin is a stomach-derived peptide hormone that acts in the brain to regulate many important physiological functions. Ghrelin receptor, named the growth hormone secretagogue receptor (GHSR), is present in many brain areas with or without obvious direct access to ghrelin circulating in the bloodstream. Ghrelin is also present in the cerebrospinal fluid (CSF) but the brain targets of CSF ghrelin are unclear. Here, we studied which brain areas are accessible to ghrelin present in the CSF. For this purpose, we centrally injected mice with fluorescein-labeled ghrelin (F-ghrelin) peptide tracer and then systematically mapped the distribution of F-ghrelin signal through the brain. Our results indicated that centrally injected F-ghrelin labels neurons in most of the brain areas where GHSR is present. Also, we detected F-ghrelin uptake in the ependymal cells of both wild-type and GHSR-null mice. We conclude that CSF ghrelin is able to reach most of brain areas expressing GHSR. Also, we propose that the accessibility of CSF ghrelin to the brain parenchyma occurs through the ependymal cells in a GHSR-independent manner.